Digital Transformation of Learning Organizations - Ifenthaler, Dirk.; Hofhues, Sandra; Egloffstein, Marc.; Helbig, Christian; SpringerLink (Online service) (Cham : Springer International Publishing : Imprint: Springer, 2021)
This open access volume provides insight into how organizations change through the adoption of digital technologies. Opportunities and challenges for individuals as well as the organization are addressed. It features four major themes: 1. Current research exploring the theoretical underpinnings of digital transformation of organizations. 2. Insights into available digital technologies as well as organizational requirements for technology adoption. 3. Issues and challenges for designing and implementing digital transformation in learning organizations. 4. Case studies, empirical research findings, and examples from organizations which successfully adopted digital workplace learning.
Preface -- Part I: Digital Transformation -- Opportunities and challenges of digital transformation for organizations; Dirk Ifenthaler -- Media literacy as driver for digital transformation; Guido Bröckling -- NN Sandra Hofhues, Christian Helbig -- Development of a maturity model for digital transformation of organizations; Dirk Ifenthaler -- Part II: International Perspectives on Learning Organizations -- Performance-oriented digital transformation; Minhong Wang -- Impact of digitization on the relevance of further education; Christian Harteis -- Harnessing big data for organizational readiness; Lisa A. Giacumo -- Conceptual change in the face of digitalization; Michael Goller -- Complex change in learning organizations; Eugene Kowch.
Keywords: School management and organization; School administration; Education Data processing; Educational technology; Organization and Leadership; Computers and Education; Digital Education and Educational Technology